Playing activities for character building in physical education learning - Muhammad Akbar Syafruddin; Nur Indah Atifah Anwar (Universitas Sebelas Maret, 2024)
A child's character is the result of good education as a whole, informal learning that takes place in the family in the form of habits that are in accordance with culture, morals and good habits, non-formal learning that occurs in society in the form of training, courses and social work, as well as formal learning what happened at school. In schools from primary to secondary level, physical education is an advanced aspect of the academic curriculum. Physical education is the pursuit of educational goals through physical exercise. Sports or non-sports activities such as playing are counted as physical activity. The method used in this article is literature study sourced from Google Scholar. Meanwhile, the conclusion in this research is that play activities that are handled well will improve physical, social and physical development. Playing with children is something they can do anywhere, anytime, and helps them grow physically and mentally.